2015
DOI: 10.1007/s11103-015-0316-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in biosynthesis of mannan polysaccharides in Dendrobium officinale by RNA-seq analysis

Abstract: Dendrobium officinale is a traditional Chinese medicinal plant. The stems of D. officinale contain mannan polysaccharides, which are promising bioactive polysaccharides for use as drugs. However, the genes involved in the biosynthesis of mannan polysaccharides in D. officinale have not yet been identified. In this study, four digital gene expression profiling analyses were performed on developing stems of greenhouse-grown D. officinale to identify such genes. Based on the accumulation of mannose and on gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 62 publications
0
64
1
Order By: Relevance
“…The stem of D. officinale is a major organ containing polysaccharides, which are promising bioactive constituents for use as drugs 6 . Analysis of the stem-specific expressed genes gives us a solid base to understand the accumulation of polysaccharides in stems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stem of D. officinale is a major organ containing polysaccharides, which are promising bioactive constituents for use as drugs 6 . Analysis of the stem-specific expressed genes gives us a solid base to understand the accumulation of polysaccharides in stems.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , mannose-1-phosphate guanylyltransferase is required by cellulose biosynthesis and identified as a member of the cellulose synthase family 21 . Several previous studies have reported that cellulose synthase family genes are associated with the biosynthesis of mannan polysaccharides 6, 22 . In D. officinale , stem-specific expression pattern of mannose-1-phosphate guanylyltransferase genes suggested their involvement in the biosynthesis of mannan polysaccharides in stem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nature, it grows as an epiphyte on trees or on rocks. Abiotic stress, such as drought, high temperature, and salinity, strongly influences the growth and development of D. officinale 1819. LEA genes have been shown to play important roles in abiotic stress responses of Arabidopsis, Oryza, Populus and other plants111216.…”
Section: Discussionmentioning
confidence: 99%
“…It grows compatibly on tree trunks in primeval forests or on damp rock of mountain climates at 500–1600 meters in warm and humid environments17. However, this orchid is easily influenced by abiotic stress, such as drought, high temperature, and salinity, causing an extremely low natural reproduction rate and slow growth in the wild181920. Therefore, it is important to understand the mechanisms underlying the response of D. officinale to abiotic stress.…”
mentioning
confidence: 99%